Answer:
No solution
Step-by-step explanation:
6X - 3Y = -9--------------(1)
- 2 X +Y= 5---------------(2)
from equation two,
Y = 5+2X------------------(3)
substitute equation (3) into equation (1)
6X-3(5+2X)= -9
opening bracket
6X-15-6X= -9
6X- 6X = -9+15
0 = 6
<h2>therefore the answer is no solution</h2>
I believe the answer is 150 miles, with a cost of $60
Let one acute angle be X and one be Y
X+Y=90 -------Eq.1
2X+12=Y
2X-Y=-12------Eq.2
solving eq 1&2 we get,
3x=78
∴X=26
substituting value X in equation.1
X+Y=90
Y=90-26
∴Y=64
⇒answer:- X=26°
Y=64°
Answer:
y = 4
Step-by-step explanation:
8(y+4)-2(y-1)=70-3y
8y+32-2y+2=70-3y
Grouping of like terms
8y-2y+3y=70-32-2
9y=36
Divide both sides by 9
9y/9 = 36/9
9 cancels itself and 9.
y=36/9
y=4
Therefore, y = 4.
Hope it helps.
If so, mark as brainliest.
Answer:
h(-1) = <u>-7</u>
Step-by-step explanation:
- use brackets while doing calculations
- steps are clearly shown in the photo
hope this helped , if i helped you in acquiring the correct answer please tag me brainliest than... have a nice day ♡